2016
DOI: 10.1155/2016/8274504
|View full text |Cite
|
Sign up to set email alerts
|

Rationale for the Successful Management of EDTA Chelation Therapy in Human Burden by Toxic Metals

Abstract: Exposure to environmental and occupational toxicants is responsible for adverse effects on human health. Chelation therapy is the only procedure able to remove toxic metals from human organs and tissue, aiming to treat damage related to acute and/or chronic intoxication. The present review focuses on the most recent evidence of the successful use of the chelating agent ethylenediaminetetraacetic acid (EDTA). Assessment of toxic-metal presence in humans, as well as the rationale of EDTA therapy in cardiovascula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 84 publications
(93 reference statements)
2
48
0
1
Order By: Relevance
“…First, to assess mercury poisoning in our patient, we decided to quantify the serum mercury concentration with ICP-MS technology because this is the method currently used to evaluate toxic-metal levels in blood and/or urine samples in humans [ 14 , 15 , 16 ].…”
Section: Discussion and Literature Revisionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, to assess mercury poisoning in our patient, we decided to quantify the serum mercury concentration with ICP-MS technology because this is the method currently used to evaluate toxic-metal levels in blood and/or urine samples in humans [ 14 , 15 , 16 ].…”
Section: Discussion and Literature Revisionmentioning
confidence: 99%
“…A common chelating agent is CaNa 2 ·EDTA [ 30 ]. It is the most commonly used chelating agent in poisoning lead and cadmium [ 15 ]. However, this drug was selected because, in addition to forming complexes that allow the elimination of mercury, several benefits have been reported on the vascular and cardiac systems [ 31 ].…”
Section: Discussion and Literature Revisionmentioning
confidence: 99%
“…However, the serious side effects that may occur during the chelation therapy such as depletion of essential minerals, prooxidant effects, hepatic and renal toxicity, and no removal of heavy metals from intracellular compartments are the major drawbacks of this treatment [3]. Since oxidative stress plays a pivotal role in the pathogenesis of metal toxicity, the use of antioxidants as a supplementary therapy to conventional chelation treatment has been proposed [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the divalent cation chelator ethylenediaminetetraacetic acid (EDTA) can destabilize the biofilm structure by interfering with the ionic attractive forces among the biofilm matrix components [13,14]. EDTA is prescribed in a number of clinical conditions demonstrating high tolerability (up to 2 g once a week, intravenously injected) and efficacy [15]. Recently, we demonstrated that the optimized semi-synthetic antimicrobial peptide lin-SB056-1 in combination with EDTA is able to exert a synergistic bactericidal effect against P. aeruginosa in an artificial sputum medium resembling CF sputum [16].…”
Section: Introductionmentioning
confidence: 99%